Strategi Kampanye Public Relations Palang Merah Indonesia (PMI) Kota Bandung dalam Meningkatkan Minat Masyarakat Kota Bandung untuk Melakukan Donor Darah Saat Pandemi Covid-19 - Hari Hidayat (Communicative : Jurnal Dakwah dan Komunikasi, 2021)
During the Covid-19 pandemic the Indonesian Red Cross (PMI) announced that blood stocks in the Blood Transparency Unit (UTD) in areas affected by Covid-19 began to experience shortages, including the city of Bandung. This is due to the increasing demand for blood from every hospital that accepts Covid-19 positive patients. The scarcity of blood stocks was caused by the fear of the public that they would donate blood during the Covid-19 pandemic. This study aims to determine the campaign strategy implemented by Public Ralations in increasing the interest of the people of Bandung to donate blood during the Covid-19 pandemic. This study also aims to determine how the management carried out by the Indonesian Red Cross (PMI) of Bandung City in increasing the interest of the people of Bandung City to donate blood during the Covid-19 pandemic. The research method used is descriptive qualitative, using data collection methods through observation, and conducting in-depth interviews, and documentation. Meanwhile, the data analysis technique used three methods according to Miles and Huberman, namely reducing data, presenting data and drawing conclusions. The implication of the results of the strategy research implemented by the public relations of the Indonesian Red Cross (PMI) in Bandung uses a strategy of publicity and a strategy of persuasion by using this strategy, the people of Bandung can find out what the benefits of blood donation are, and the interest in blood donors in Bandung is also increasing. For future researchers, it is hoped that this research will become a source of reference and inspiration to develop and continue similar research on public relations campaign strategies. Keywords : Covid-19,Public Relations,Campaign Strategy.